Development of the advised protocol for OCT study terminology and elements anterior segment OCT extension reporting guidelines (APOSTEL-AS): Study protocol - Ameenat Lola Solebo; Marcus Ang; Alice Bellchambers; Colin J. Chu; Alastair K. Denniston; Laura E. Downie; Thomas Evans; Alexander S. Fraser; Scott Hau; Alex S. Huang; Pearse A. Keane; Xiaoxuan Liu; et al. (PLoS ONE, 2025)
Background Anterior segment optical coherence tomography (AS-OCT) is emerging as a valuable diagnostic, monitoring and predictive tool. Clinical utility has been suggested for ophthalmic disorders such as glaucoma, corneal disease, cataract and uveitis, which taken together comprise the majority of the blinding conditions affecting working age individuals globally. anterior segment is an obstacle to reproducibility and interoperability. To provide this guidance, we aim to extend the existing Advised Protocol for OCT Study Terminology and Elements (APOSTEL) guidelines, to ensure applicability to AS-OCT. Methods In line with EQUATOR Network guidance for the development of reporting guidelines, APOSTEL-AS will be developed through a staged consensus process involving literature review and Delphi consensus across an international multi-disciplinary stakeholder group, overseen by a multi-disciplinary multi-national Steering Committee. The systematic scoping review will be used to generate candidate items, support the development of a consensus nomenclature for AS-OCT representation of ocular structure, and to form Delphi group membership. Delphi methodology, used to consider items for inclusion, rewording or exclusion, will be undertaken in line with ACCORD (ACcurate COnsensus Reporting Document) guidance, with at least two rounds of Delphi survey, inclusion consensus threshold set at 80%, and steering committee reviews between rounds. The resultant APOSTEL-AS guideline will undergo piloting before dissemination of the final version. Discussion The APOSTEL-AS checklist, with minimum and recommended items to be reported about study methods, should provide timely support for researchers to ensure future standardisation, interoperability and reproducibility of reported work, hastening implementation and the translation of knowledge into clinically beneficial action.